An Inclusive Pedagogical Approach in Teaching Dance for People with Disabilities at the Guriang Tujuh Studio - Nurul Aulia Dwi Oktaviani; Alis Triena Permanasari; Wiwin Purwinarti (CV. Edujavare Publishing, 2026)
Education is a process to develop human resources which is carried out systematically and in stages. This study aims to analyze the implementation of inclusive pedagogy in dance instruction for persons with disabilities at Sanggar Guriang Tujuh, Lebak, Banten. This research employs a descriptive qualitative approach, with data collected through participatory observation, in-depth interviews, and documentation. The findings reveal that inclusive pedagogy is implemented through adaptive teaching strategies utilizing demonstration, imitation, and drill methods, combined with differentiated instruction and multisensory approaches. The learning process is no longer oriented toward rigid movement standards but instead accommodates the diverse physical and sensory abilities of learners. The results also indicate that this approach fosters a participatory and non-discriminatory learning environment while enhancing motor skills, self-confidence, and artistic expression among participants with disabilities. Furthermore, Sanggar Guriang Tujuh functions as an alternative space that not only serves as an art learning center but also as an inclusive social laboratory that promotes social integration and individual empowerment. This study contributes theoretically to the development of inclusive pedagogy in arts education and practically to community-based inclusive dance learning models grounded in local cultural values.